2013
DOI: 10.1111/desc.12029
|View full text |Cite
|
Sign up to set email alerts
|

Development of ordinal sequence perception in infancy

Abstract: Perception of the ordinal position of a sequence element is critical to many cognitive and motor functions. Here, the prediction that this ability is based on a domain-general perceptual mechanism and, thus, that it emerges prior to the emergence of language was tested. Infants were habituated with sequences of moving/sounding objects and then tested for the ability to perceive the invariant ordinal position of a single element (Experiment 1) or the invariant relative ordinal position of two adjacent elements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
(85 reference statements)
0
7
0
1
Order By: Relevance
“…Our ability to rapidly extract structured sequential information from the environment underpins many complex behaviors—from language development and social interaction to intuitive decision‐making (e.g., Lewkowicz, 2013). Processing of sequential information is critical to adapt to a spatiotemporally bounded environment, and many studies investigated its ontogenetic and phylogenetic roots (Wilson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our ability to rapidly extract structured sequential information from the environment underpins many complex behaviors—from language development and social interaction to intuitive decision‐making (e.g., Lewkowicz, 2013). Processing of sequential information is critical to adapt to a spatiotemporally bounded environment, and many studies investigated its ontogenetic and phylogenetic roots (Wilson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 10 ]). Lewkowicz [ 11 ] claims that “various findings on the effects of early experience demonstrate unequivocally that the young nervous system is highly plastic and that it depends on exposure to temporally and spatially aligned multisensory inputs for the development of normal multisensory functions” (p. 6). This position is supported by a variety of studies (in both animal models and special populations, such as children born deaf and later receiving cochlear implants) suggesting that limited input from one of the senses early in development limits sensitivity to multisensory integration even when that sense is later recovered (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, these studies have found that infants younger than 8 months of age can detect adjacent FIGURE 3 Mean duration of looking at the hierarchical and non-hierarchical patterns in the Familiar and Generalization test trials, respectively, in the 8-to 10-and 12-to 14-month-old infants in Experiment 1. Error bars indicate SEM and asterisks indicate a statistically significant difference in looking at the two types of patterns sequence statistics but that they do not detect ordinal position information nor simple rules (Frank, Slemmer, Marcus, & Johnson, 2009;Lewkowicz, 2013;Lewkowicz & Berent, 2009;Marcus et al, 1999). Therefore, we predicted that 4-to 6-month-old infants would not exhibit successful learning and generalization of the hierarchical serial patterns presented in Experiment 1.…”
Section: Methodsmentioning
confidence: 90%
“…As noted earlier, prior studies have found that relatively young infants generally only exhibit the simplest forms of pattern learning. For example, these studies have found that infants younger than 8 months of age can detect adjacent sequence statistics but that they do not detect ordinal position information nor simple rules (Frank, Slemmer, Marcus, & Johnson, ; Lewkowicz, ; Lewkowicz & Berent, ; Marcus et al, ). Therefore, we predicted that 4‐ to 6‐month‐old infants would not exhibit successful learning and generalization of the hierarchical serial patterns presented in Experiment 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation